Efektifitas Penegakan Undang-Undang Nomor 1 Tahun 1974 Tentang Perkawinan Terhadap Pernikahan Siri - Maria Ana Liwa; Eli Tri Kursiswanti; Yanuel Albert Faisan (Collegium Studiosum Journal, 2022)
Marriage is actually a momentum to share happiness with others, share the legality and romance of happiness as a married couple. But not infrequently couples have to cover up their happiness through unregistered marriages. Several factors that cause someone to do unregistered marriage such as age that is not enough as recommended by the government, economic problems and the most ironic is polygamy. Siri marriage is a form of marriage that is carried out under the hands based on religious teachings, customs and without official recognition from state law, because it is not registered in state-owned institutions. The author uses the library research method or literature review. This literature review research is conducting research from library books, magazines, journals and articles and sources from the internet that are relevant to the problems discussed.